Coberturas comestíveis a base de quitosana e fécula de mandioca : desenvolvimento e impacto sobre a qualidade sensorial e vida de prateleira da mangaba (Hancornia speciosa Gomes) - Souza, Jane Delane Reis Pimentel (2012)
Mangaba (Hancornia Speciosa) is a fruit highly appreciated in the Brazilian Northeastern, a region which concentrates most of the fruit’s domestic production. Unfortunately, it is extremely perishable, which restricts its consumption and industrialization. One alternative that has been used to prolong the shelf life of fruits is the use of edible coatings, especially those containing chitosan, a material that has proved to be a good barrier to water, CO2 and O2, and in some cases, to have antimicrobial action. The objective of this study was to develop a mixed coating, based on cassava starch and chitosan, for the conservation of mangaba. Through central composite rotational design (CCRD), 9 different formulations of edible coatings were developed, taking as independent variables the concentrations of cassava starch and chitosan in the coating. As dependent variables, the following parameters were used: weight loss, soluble solids, pH, acidity, texture instrumental color (L*, a* and b*), and the degree of ripeness of the fruit, evaluated by trained judges, through the appearance and firmness of the mangabas. The fruits were treated with the coatings and stored at 21°C for 10 days. Linear regressions between the storage time and the values of each parameter-physical, physical-chemistry, instrumental and sensory- allowed to estimate the rate of changes occurred in the weight, the color, the degree of maturation of the fruits among others, during the storage of fruits. Response surface methodology applied to the data revealed that, while cassava starch significantly reduced (p ≤ 0.05) the rate of change in the color parameter a *, the chitosan significantly reduced (p ≤ 0.05) theloss weight of fruits. Multivariate analysis of the data using Principal Component Analysis (PCA) allowed us to observe a negative correlation (p = 0.0108) between the concentration of chitosan present in the coatings and the 1st component, which was associated with the rate of changes occurred in the weight, the color parameters (L *, a *, b *) and the degree of maturation of the fruits (appearance and firmness), indicating that, at the concentrations studied, the higher the level of addition of chitosan added to the coating, the smaller the changes suffered by mangabas stored at 21°C in relation to the mentioned parameters. Additional tests conducted in the optimization region, confirmed that mangabas treated with 2% of cassava starch and 1.5% chitosan and stored at 21°C had lower rates of weight loss, color changes (L *, a *; b *) and best preserved the sensory attributes of appearance and firmness. Mangabas with and without coating, and stored at 10°C, suffered injury in their appearance, as reported by the trained judges. Validation studies conducted using both commercial chitosan and chitosan prepared at the Federal University of Sergipe (UFS), revealed that the two materials showed similar effect in delaying the ripening of mangabas, increasing the shelf life of the fruit from 3 to 5 days, and inhibiting the growth of total and fecal coliforms. None of the coatings prepared with cassava starch (2%) and chitosan (1.5%) -commercial or UFS- altered the sensory characteristics of the juice produced from the mangabas studied.